The Contributing Factors of Students' Speaking Anxiety in EFL Classroom Presentation - ‘Aathifah, Alya; Sundari, Hanna; Retnomurti, Ayu Bandu (JADEs Journal of Academia in English Education, 2023)
The purpose of this study was to analyze the characteristics of students who experience anxiety in speaking English in the presentation class and to analyze the external factors that cause students' speaking anxiety in the presentation class at SMA Negeri 51 Jakarta class XI IPS 4. This study used a thematic qualitative descriptive analysis. by using the theory of Rogers (2008) in analyzing the characteristics of anxiety and Tanveer (2007) in analyzing the external factors that cause anxiety. The first data was obtained from the results of observations which were carried out once by documenting class presentation activities then the researcher analyzed them, and the second data was obtained through interviews conducted online using WhatsApp chat which were conducted outside school hours. In the first data, the researcher found that there were characteristics of anxiety in class XI IPS 4 students which could be seen from three aspects, namely physical aspects, emotional aspects, and psychological aspects. Meanwhile, the second data found that external factors causing students' speaking anxiety in class XI IPS 4 in the presentation class were caused by two components, namely the audience component and the material component.